PELATIHAN PENGOLAHAN JAMUR TIRAM MENJADI KRIPIK JAMUR TIRAM DI DESA LEBAH SEMPAGE - Lale Fichear Neoningratheof; Mardiah, Al Aina Ul; Aeni, Yuli; Dewi, Cindra; Putri, Nabilah Tsabitah; Fitriani, Fitriani; Ramadhan, Anugrah; Putra, Sonny Manggala; Hamdi, M. Faizin Ilham; Dinata, Lalu Alfito; Alamsyah, Ahmad (Universitas Mataram, 2025)
Lebah Sempage Village is rich in crops, especially from plantations, agriculture, livestock, and natural beauty. One of the products produced is oyster mushroom chips, which has been cultivated since 2016 by the Women Farmers Group (KWT) by utilizing sawdust waste. However, the number of oyster mushroom processors is decreasing because many choose to sell them directly to collectors. To overcome this, an innovative participatory based training was held with the aim of motivating the community to be more creative in processing crops, especially oyster mushrooms. This training succeseded in changing mindsets, improving skills, and encouraging community independence in managing oyster mushroom products.